Genetic relationship of Coccinia grandis (L.) Voigt accessions, based on RAPD and ISSR markers - Kittiwongwattana, Chokchai (Science, Engineering and Health Studies, 2022)
Coccinia grandis (L.) Voigt or ivy gourd is widely distributed in nature and has potential for medicinal uses. However, there is little information on the genetic diversity of wild populations in Thailand. Here, 15 ivy gourd accessions were collected from Bangkok and nearby provinces. Angled and lobed leaves were observed. DNA fingerprints were generated from twelve random amplified polymorphic DNA (RAPD) and twelve inter-simple sequence repeat (ISSR) primers. The level of polymorphism in the RAPD profiles was higher than that of the ISSR profiles. Dice’s similarity coefficient from RAPD data ranged from 0.73 to 0.82 and was lower than that from the ISSR data (0.88-1.00). The unweighted pair group method with arithmetic mean dendrogram, based on combined RAPD and ISSR data, was similar to the RAPD dendrogram but distinct from the ISSR dendrogram. Two major clusters were found with eleven and four accessions. The genetic relationship between some accessions was relatively consistent with either their locations or leaf shapes. The result indicated that the RAPD and ISSR techniques were suitable for the genetic study of ivy gourd. It also provided the basis for future studies with a higher number of samples for a better understanding of ivy gourd genetic diversity in Thailand.